Recursive Bayesian estimation of autoregressive model with uniform noise using approximation by parallelotopes - Pavelková, Lenka; Jirsa, Ladislav (International journal of adaptive control and signal processing, 2017)
Summary This paper proposes a recursive algorithm for the estimation of a stochastic autoregressive model with an external input. The noise of the involved model is described by a uniform distribution. The model parameters are estimated using the Bayesian approach. Without an approximation, the support of the posterior distribution is a complex multidimensional polytope whose number of faces increases with time. We propose an approximation of this polytope in each time step by a parallelotope with a constant number of faces. The behaviour of the proposed algorithm is illustrated by simulations and compared with other methods.